Leishmania spp. em hospedeiros reservatórios: meta-análise, aspectos epidemiológicos e moleculares - Ratzlaff, Fabiana Raquel (2023)
Leishmaniosis is an infectious parasitic disease, caused by protozoa of the genus Leishmania, with cutaneous, mucocutaneous and/or visceral clinical manifestation, with acute or chronic development, maintained between wild and urban reservoirs, vectors, and humans. The disease has a worldwide distribution, and has shown important changes in the pattern of transmissibility. Human interaction with the wild environment and fauna, caused by the expansion of agricultural frontiers, cities, or tourism, combined with environmental changes, provided a greater adaptability of the parasite to infect a variety of animal species, and a perfect adaptation of the vector to the urban environment, aggravating the sanitary problem. Diptera can infect domestic, wild and synanthropic mammalian species, representing a great risk to the human population. In this context, Brazil has been showing a significant increase in the number of cases diagnosed in humans and animals. Thus, the objective of this work was to identify possible hosts and/or reservoirs of Leishmania spp. in the country, different from the dog and the man. Therefore, a systematic review with meta-analysis was carried out, seeking studies that identified the different species of Leishmania circulating in the wild, peri-domestic, and domestic environments, acting directly in the epidemiology of the disease and in the maintenance of endemicity in Brazilian regions. Therefore, 229 species of possible hosts or reservoirs were identified, highlighting the horses with the highest occurrence. It should be noted that among the animals studied in Brazil, other species infected in the Brazilian regions stood out as potential reservoirs of Leishmania spp.: domestic felines, rodents, marsupials, and bats. The molecular method was the most used, identifying 25% of the individuals sampled infected with some species of the protozoan, namely: Leishmania spp. most frequent, followed by Leishmania (Leishmania) infantum, Leishmania (Viannia) braziliensis and Leishmania (Leishmania) amazonensis. The order Chiroptera, composed of several species of bats, flying mammals with a great ability to move and adapt to different environments and synanthropic habits, has become important for research on Leishmania spp. in Brazil and in the world. Through systematic review, bats infected with Leishmania spp. in the following Brazilian states: Maranhão, Mato Grosso do Sul, Minas Gerais, Espírito Santo and São Paulo. The role of these animals in the epidemiological cycle of leishmaniasis has been recognized as being potential reservoirs and could harbor the protozoan in endemic and non-endemic areas of Rio Grande do Sul. Thus, it was identified for the first time, through molecular techniques, sequencing and development of the phylogenetic tree, the presence of natural infection by Leishmania spp. and Leishmania (L.) infantum in bats of the species Tadarida braziliensis and Molossus molossus, from different locations in the state. These animals can serve as a source of infection for insect vectors that, consequently and proximity, can infect humans and domestic animals. However, further studies are needed to determine the role of these mammals in the epidemiology and transmission of leishmaniasis. Therefore, it is fundamental to know the species of animals involved in the biological cycle of the protozoan, in order to constitute environmental biomarkers, as well as to identify the species of Leishmania to plan actions and control measures.